2017
DOI: 10.1002/app.44862
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning of porous polylactic acid fibers during nonsolvent induced phase separation

Abstract: In this study, porous micron‐sized fibers of polylactic acid (PLA) are fabricated via electrospinning of PLA‐dichloromethane (DCM)‐hexane systems with no post treatment involved. Several compositions from the liquid‐liquid phase separated region of the phase diagram of this ternary system are selected and their electrospinnability are investigated throughout their phase separation process before gelation. We show that under constant processing and ambient parameters, there is a phase separation shelf time for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
81
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(81 citation statements)
references
References 29 publications
0
81
0
Order By: Relevance
“…However, the resultant PLA fibres lacked well-defined pores and uniform structures. In a recent paper, Rezabeigi et al [38] produced porous, micron-sized fibres of PLA by electrospinning PLA-DCM-hexane systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, the resultant PLA fibres lacked well-defined pores and uniform structures. In a recent paper, Rezabeigi et al [38] produced porous, micron-sized fibres of PLA by electrospinning PLA-DCM-hexane systems.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the pore formation and pore morphology, including fiber diameter and surface morphology, depended on the electrospinning parameters, with applied voltage being the most important parameter. Rezabeigi et al produced porous polylactic acid (PLA) microfibers with various morphologies via the one‐step electrospinning of liquid–liquid phase‐separated PLA‐dichloromethane‐hexane systems. The differences in solvent evaporation rates caused composition changes in the electrospinning jet after ejection, leading to the formation of a two‐phase region and, consequently, the formation of pores.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a slight reduction in surface tension is also observed for this solution, which can be the result of polymer degradation causing a decrease in cohesive forces between the solution molecules. Lower surface tension however is known to positively affect the electrospinnability of a solution . On the other hand, the conductivity and pH values continue to increase and decrease, respectively, during the first 2 days after PEPT.…”
Section: Resultsmentioning
confidence: 99%